DAMPAK ETIKA UANG TERHADAP PERILAKU KECURANGAN PAJAK DENGAN GENDER SEBAGAI VARIABEL MODERASI (Studi pada Wajib Pajak Orang Pribadi di KPP Pratama Kudus) - Anita Yulinar, 14.05.52.0208; Meita Oktaviani, Rachmawati (Students Journal of Accounting and Banking, 2018)
This study aims to examine and analyze the influence of money ethics to tax evasion. In addition to testing and analyzing the influence of intrinsic religiosity, intrinsic extrinsic as a moderator of the relationship between money ethics and tax evasion.The primary data research method used is distributing questionnaires to 120 individual taxpayers in KPP Pratama Kudus. The sampling technique used is convenience sampling. Data analysis technique used is regression moderation test of absolute difference by using program of SPSS.Result of research indicate that money ethics have positive effect to tax evasion, In relationships gender as moderating variables. Gender does not succeed in moderating the positive relationship between money ethics and tax evasion.Keywords: Money Ethic, Gender, Tax Evasion